PENGAWASAN MASYARAKAT ADAT PADA PELAKSANAAN PEMBANGUNAN DI DISTRIK TIOM KABUPATEN LANNY JAYA - TABUNI, WERNICE; PANGKEY, MASJE; RURU, JOORIE (Sam Ratulangi University, 2018)
Abstract: tiom District as one of the districts Lanny Jaya Regency, in the implementation of developmentremains experiencing barriers due to constraints in planning exercises. Besides, coordination betweenthe various government officials not run properly, how to work the expected effect control these thingslead. the achievement of development goals do not always go as expected. Therefore, to meet themaximum goal achievement, government management functions include planning, coordinating andmonitoring the implementation of development must get the attention it heartily. So the maincharacteristic is the human resource development activities aimed at behavior change. This study aimedto analyze the leadership of the District in the implementation of human resource development in theDistrict Tiom Lanny Jaya Regency. The research method is qualitative. Primary data is depth interviewswith 11 informants. The secondary data is literature, articles, journals, as well as the internet sites thatare pleasing to the research conducted. Informant selection technique consists of, the district secretaries,three section heads, three subsections two staff members, one village head, one headman. Methods ofdata collection observation (observation), the state of the environment outside the district or districts,interviews researchers dig as much data related to the subject matter. Data analysis technique. The datacollected and predict data from various sources, ie in-depth interviews, direct observation, which waswritten by the remarks field. Data was analyzed as a whole and make marginal notes about the data thatis deemed necessary and in accordance also with the objectives and purposes of research. Motivation isan inner drive that generate power or energy that humans behave mobilizing to achieve the goal, theproper motivation can achieve the objectives of individuals and bureaucratic objectives.Keywords: The Head of tde Dstrict LeadershipStile on Implementation of Human ResourcesDeploment in the District Tiom Lanny Jaya Regency papua Province.